Incomplete lineage sorting and long-branch attraction confound phylogenomic inference of Pancrustacea - Yu, Hiu Yan; Chu, Ka Hou; Tsang, Ling Ming; Ma, Ka Yan (Frontiers in Ecology and Evolution, 2024)
The phylogenetic relationships within Pancrustacea (including Crustacea and Hexapoda) remain elusive despite analyses using various molecular data sets and analytical approaches over the past decade. The relationship between the major lineages of Allotriocarida, which includes Hexapoda, the most species-rich animal taxon, is particularly recalcitrant. To investigate and resolve the root of phylogenetic ambiguity in Pancrustacea, we re-evaluated the evolutionary relationships of major pancrustacean clades using a phylogenetically informed orthology approach and assessed the effect of systematic errors, with a major focus on long branch attraction (LBA) and incomplete lineage sorting (ILS). A data set comprising 1086 orthologs from 106 species representing all major extant classes of pancrustaceans was assembled and used in gene tree and species tree construction after various filtering processes. Regardless of the filtering criteria and phylogenetic analyses, the resulting trees consistently supported (1) a sister relationship of Remipedia and Hexapoda (hence rejecting the monophyly of Xenocarida, i.e. Remipedia + Cephalocarida), and (2) refuted the monophyly of Multicrustacea, as Copepoda is either sister to or nested within Allotriocarida. Examination of gene trees reveals that the grouping of Multicrustacea and Xenocarida in previous phylogenetic studies may represent LBA artefacts. Phylogenetic signal analyses suggest a low resolution and an incidence of strong conflicting signals at the deep splits. Further analyses indicate a partial contribution of incomplete lineage sorting (ILS) to the contradictory signal in the allotriocaridan phylogeny, leading to limited support for any potential relationships between Branchiopoda, Cephalocarida and Copepoda. This study suggests the need for further examination of other potential sources of signal discordance, such as introgression and gene tree estimation error to fully understand the evolutionary history of Pancrustacea.